2020
DOI: 10.1029/2020jd032550
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Surface Heterogeneity‐Induced Convection Using Cluster Analysis

Abstract: Land-atmosphere interactions and boundary layer processes often control the formation of shallow clouds and subsequently deep convective precipitation over the U.S. Southern Great Plains. In this study, we examine the impacts of large-scale advection on the cloud populations and land-atmospheric coupling observed during the Holistic Interactions of Shallow Clouds, Aerosols, and Land-Ecosystems field campaign in 2016. We performed two large eddy simulations using the Weather Research and Forecasting Model for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…We limit our analysis to the time period between 1000 and 1100 CST; specifically, we evaluate the average of 1000, 1015, 1030, and 1045 CST instantaneous outputs, referred to as the “1000 CST period” in the following. This is when the average z i already grows to be ∼1.5 km, an equilibrium height that remains the same in the afternoon, while clouds have not matured yet at this time to obscure the forcing from the surface to the atmosphere (Chen et al., 2020; Fast, Berg, Feng et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We limit our analysis to the time period between 1000 and 1100 CST; specifically, we evaluate the average of 1000, 1015, 1030, and 1045 CST instantaneous outputs, referred to as the “1000 CST period” in the following. This is when the average z i already grows to be ∼1.5 km, an equilibrium height that remains the same in the afternoon, while clouds have not matured yet at this time to obscure the forcing from the surface to the atmosphere (Chen et al., 2020; Fast, Berg, Feng et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to retain the same land cover as Fast, Berg, Feng et al (2019) because strong dependence of evaporative fraction on the vegetation cover has been suggested for the SGP site (Williams & Torn, 2015). Readers are also referred to Chen et al (2020) for the influence of land cover heterogeneity on the cloud development for the same HI-SCALE case. Surface topography is another important forcing, which we exclude from our main simulations to interpret atmospheric response to the imposed surface heterogeneities without other confounding effects.…”
Section: Tablementioning
confidence: 99%
“…The median shows more intense radiative cooling during the ShCu regime than for ShDeep. For example, Edwards et al (2014), using large-eddy simulations, showed that radiative cooling has an important effect on the morning transition and in the development of the convective BL. The mechanical turbulence is seen in Fig.…”
Section: Event Datementioning
confidence: 99%
“…Continental shallow cumulus clouds (ShCu) are tightly coupled with the land surface and have strong impacts on the surface energy partition and the turbulent transport of momentum, heat, and moisture [1][2][3][4][5][6]. They are also important for their seeding role in transitioning into hot-tower deep convective clouds with heavy precipitation [7].…”
Section: Introductionmentioning
confidence: 99%
“…2021, 13, 2309 2 of 19 albedos, surface roughness, soil moisture content, and leaf area index. This is because: (1) ShCu strongly interact with the surface heating and moistening driven by the diurnally varying solar and infrared radiation; (2) observations of the initiation and continuous development of ShCu are needed to study the mechanisms controlling the transition from shallow to deep convection; (3) cloud size is important as larger clouds can grow deep and rain more easily [17]; and (4) ShCu may form preferentially over certain land surface properties or land cover types [18,19].…”
Section: Introductionmentioning
confidence: 99%